Lost in translation: western representations of Māori knowledge - Carl Mika (Open Review of Educational Research, 2017)
We recently attended a conference at which a non-Māori presenter, drawing on a particular metaphor already established by Māori writers, related Māori natural world features to a research method. The presentation was useful because it highlighted several issues that call for our concern as Māori philosophers. In this article, we outline these concerns, which are: first, that a blunt response to such a presentation is not undertaken lightly from a Māori viewpoint; and, second, that the presenter’s talk exemplifies a wider problem of warping Māori concepts and labels to fit a Western philosophical approach. We call this latter problem ‘Translation’, because it involves moving the Māori world and its phenomena over into one that is palatable for policy and research. The aim of the article is not to single out the presenter, but rather to refer to his presentation in order to consider the prior issue of Translation. In cases where Translation occurs, a Māori critical philosophical stance is clearly needed, in order to both investigate the warping of Māori thought on which it relies, and review the place of Māori philosophy and philosophical response in the arena of educational research.